Vertical adhesion force between particle and different positions on bubble surface. (1st April 2021) - Guo, Fangyu; He, Qi; Xing, Yaowen; Zhang, Youfei; Ding, Shihao; Xu, Mengdi; Gui, Xiahui
Graphical abstract: Highlights: Vertical adhesion force between particle and bubble was measured. Vertical adhesion force always decreased with increasing offset distance. Bubble behaved as a Hooke's spring under a vertical force. Abstract: Bubble-particle detachment is the key sub-process for determining the upper size limit of flotation. In this study, vertical adhesion force between particle and different positions on a bubble surface were measured using a micro-mechanical testing machine (MMTM). Three micrometer glass beads with varying hydrophobicities (hydrophilic, medium hydrophobic, and highly hydrophobic) were adhered to the end of the force sensor, and an air bubble with a diameter of 950 μm was fixed at the bottom of the hydrophobic quartz cell. Different contact positions were selected by gradually increasing the offset distance from the vertical axis of the bubble. The results showed that the back-calculated advancing contact angles of the hydrophilic, medium hydrophobic, and highly hydrophobic particles were 45, 86, and 124°, respectively. The vertical adhesion force always decreased with increasing offset distance, regardless of particle hydrophobicity. The decrease in the vertical component of the normal capillary force at the contact point might be the main reason for the decreased vertical adhesion force. Additionally, a linear region in the retraction force curves was always observed, illustrating that the bubble behaved as a Hooke's spring under a vertical force. The spring constants at different positions on the bubble surface were found to decrease with increasing offset distance, which were consistent with the variations in vertical adhesion force observed.